Profit Management with Modern Hotel Business ICT Tools - Alicja GRZEŚKOWIAK; Piotr PETERNEK; Bartosz FORYSIAK (Communications of International Proceedings, 2025)
The issue of operational profitability has been the subject of interest for many authors. In the hotel industry, for many years, the focus was primarily on revenue optimization based on the widely used RevPAR indicator. However, the global crisis caused by the pandemic accelerated additional processes and highlighted the need for hotel business managers to pay greater attention to operational costs. As a result, operational goals are shifting from revenue optimization to profit optimization, with GOPPAR becoming the primary analytical indicator. The aim of this paper is to present the possibilities and needs of using dedicated computer systems to integrate cost and revenue data from all hotel systems to create a "profit management" tool. This tool not only facilitates reporting and controlling but also enables dynamic decision-making using simulation methods and basic forecasting techniques.
Keywords: hotels; profit management; ICT solutions; cost and revenue analysis; hospitality industry; proUSALI